Local anesthesia with lidocaine 2% or articaine 4% in maxillary permanent first molars with Molar Incisor Hypomineralization (a randomized clinical study) - مي حيدر; نبيه رسلان (Latakia University Journal -Medical Sciences Series, 2023)
Objectives: Comparison of lidocaine 2% and articaine 4% in terms of injection pain and efficacy of anesthesia in children with Molar Incisor Hypomineralization (MIH). Materials and Methods: The sample included 7 children. Each child randomly received lidocaine 2% or articaine 4% in the first session, with the other solution used in the second. The two scales used are: the WBF Subjective Scale and the FLACC Behavioral Scale. Results: Articaine injection was more painful than lidocaine in buccal and/or palatal infiltration without a statistically significant difference according to both scales. Both solutions were effective when treating MIH-maxillary molars with no statistical difference according to the WBF scale. Although the mean pain value for lidocaine (2.2±1.89) was lower compared to articaine (3.4±1.13( according to the FLACC scale, the difference was not statistically significant. Conclusion: There is no difference between the two solutions in terms of injection pain. Lidocaine is more effective than articaine in anesthetizing MIH-maxillary